Detection of β-amyloid peptide (1–16) and amyloid precursor protein (APP770) using spectroscopic ellipsometry and QCM techniques: A step forward towards Alzheimers disease diagnostics - Mustafa, M. K.; Nabok, Alexei; Parkinson, D.; Tothill, Ibtisam E.; Salam, Faridah; Tsargorodskaya, A. (Elsevier, 2010)
A highly sensitive method of spectroscopic ellipsometry in total internal reflection mode (TIRE) was exploited for detecting β-amyloid peptide (Aβ1–16) in the direct immune reaction with monoclonal DE2 antibodies (raised against Aβ1–16) electrostatically immobilised on the surface of gold. A rapid detection of Aβ1–16 in a wide range of concentrations from 5 μg/ml down to 0.05 ng/ml was achieved using a cost-effective and label-free direct immunoassay format. TIRE dynamic spectral measurements proved that the immune reaction between DE2 monoclonal antibodies and Aβ1–16 is highly specific with the affinity constant KD = 1.46 × 10−8 mol/l. The same DE2 antibodies were utilised for detection of amyloid precursor protein APP770, a larger protein containing Aβ1–16 domain, using the quartz crystal microbalance (QCM) measurements in liquid. A combination of QCM and TIRE kinetics results allowed the evaluation of the originally unknown concentration of APP770 in complete medium solution containing other proteins, salts, and amino acids.
Keywords: Alzheimer's disease; β-Amyloid peptide 1–16; Amyloid precursor protein (APP770); Direct immunoassay; Total internal reflection ellipsometry; Quartz crystal microbalance